2012
DOI: 10.1242/jeb.073577
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acute temperature stress on hemocytes of invasive and native mussels (Mytilus galloprovincialisandM. californianus): DNA damage, membrane integrity, apoptosis and signalling pathways

Abstract: SUMMARYWe investigated the effects of acute heat stress and cold stress on cell viability, lysosome membrane stability, double-and singlestranded DNA breakage, and signaling mechanisms involved in cellular homeostasis and apoptosis in hemocytes of native and invasive mussels, Mytilus californianus and Mytilus galloprovincialis, respectively. Both heat stress (28, 32°C) and cold stress (2, 6°C) led to significant double-and single-stranded breaks in DNA. The type and extent of DNA damage were temperature and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 50 publications
4
59
0
1
Order By: Relevance
“…Specifically, valve gaping during recovery would permit more efficient aerobic ATP generation to fuel macromolecular repair. This prediction corresponds well with gene and protein expression data indicative of damage to proteins (induction of heat shock proteins and proteasome constituents) (Buckley et al, 2001;Gracey et al, 2008;Lockwood et al, 2010;Tomanek and Zuzow, 2010), and it is further supported by the discovery that thermal stress leads to significant increases in single-and double-stranded DNA breakage (Yao and Somero, 2012). Other gene expression studies have indicated alternating phases of oxidative and reductive metabolism in M. californianus (Connor and Gracey, 2011;Gracey et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Specifically, valve gaping during recovery would permit more efficient aerobic ATP generation to fuel macromolecular repair. This prediction corresponds well with gene and protein expression data indicative of damage to proteins (induction of heat shock proteins and proteasome constituents) (Buckley et al, 2001;Gracey et al, 2008;Lockwood et al, 2010;Tomanek and Zuzow, 2010), and it is further supported by the discovery that thermal stress leads to significant increases in single-and double-stranded DNA breakage (Yao and Somero, 2012). Other gene expression studies have indicated alternating phases of oxidative and reductive metabolism in M. californianus (Connor and Gracey, 2011;Gracey et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…This suggests disruption of the membrane integrity of the gut, allowing algae to leak into the pseudocoelom. This is consistent with the finding that heat and cold stress caused a decrease in membrane stability in mussels (Yao & Somero 2012). …”
Section: Discussionsupporting
confidence: 93%
“…While some studies show this component of the immune function can be increased at warmer environmental temperatures (Truscott and White 1990; Chu and Lapeyre 1993), the decrease in hemocyte numbers found here may be related to its viability or stress‐induced damage (such as apoptosis) in a warmer environment (Yao and Somero 2012; Diaz et al. 2013).…”
Section: Discussionmentioning
confidence: 68%